2014
DOI: 10.1186/1742-6405-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Influence of providers and nurses on completion of non-targeted HIV screening in an urgent care setting

Abstract: IntroductionDespite recommendations by the Centers for Disease Control (CDC) that all adults be offered non-targeted HIV screening in all care settings, screening in acute-care settings remains unacceptably low. We performed an observational study to evaluate an HIV screening pilot in an academic-community partnership health center urgent care clinic.MethodsWe collected visit data via encounter forms and demographic and laboratory data from electronic medical records. A post-pilot survey of perceptions of HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Indeed, a systematic screening for comorbidities may take up to an hour,14 particularly when undertaken for the first time. However, for subsequent screenings (eg, 1 or 2 years later), the process should be quicker and will be more efficient if the initial screening is easily available (eg, if these data are available in the medical records or in electronic form) 76. We are aware that the reporting form is detailed and long, but this could be implemented as a hierarchical form (ie, with sections to be filled-in only if relevant).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a systematic screening for comorbidities may take up to an hour,14 particularly when undertaken for the first time. However, for subsequent screenings (eg, 1 or 2 years later), the process should be quicker and will be more efficient if the initial screening is easily available (eg, if these data are available in the medical records or in electronic form) 76. We are aware that the reporting form is detailed and long, but this could be implemented as a hierarchical form (ie, with sections to be filled-in only if relevant).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the National Hospital Ambulatory Medical Care Survey revealed that HIV testing was significantly greater in outpatient ambulatory medical care settings than in emergency departments (ED) and physicians’ offices, suggesting that urgent cares may be an important setting in which to expand testing. 9 10 HCV has been identified in individuals outside of current CDC recommendations for testing, indicating a need to implement universal screening during patient visits. 11 Multiple studies have demonstrated success in using a best practice alert (BPA) model, prompting and streamlining the linkage-to-care process.…”
Section: Introductionmentioning
confidence: 99%